Development of a microstent system for minimally invasive glaucoma surgery - Siewert Stefan; Schmidt Wolfram; Kaule Sebastian; Kohse Stefanie; Stiehm Michael; Kopp Franziska; Stahnke Thomas; Guthoff Rudolf; Grabow Niels; Schmitz Klaus-Peter (Current Directions in Biomedical Engineering, 2017)
Glaucoma is the leading cause of irreversible blindness worldwide. An increased intraocular pressure (IOP) is known as major risk factor. Currently, drainage devices that are implanted by means of minimally invasive glaucoma surgery (MIGS) represent a promising approach for IOP low-ering. Commercially available devices for MIGS suffer from unregulated drainage involving ocular hypotony. Further-more, long term drainage capability of current devices is limited by fibrotic encapsulation processes. Therefore, our group focusses on the development of a valved drug-eluting microstent for MIGS. Within the current work, we developed two alternative injector devices for minimally invasive mi-crostent implantation. Both injector devices were based on a cannula in which the microstent is loaded and a mandrel inside the cannula. Injector device A is designed to push the microstent out of the cannula and injector device B is de-signed to withdraw the cannula above the microstent. Manu-facturing of injector devices was conducted using rapid prototyping. Simplified polymeric microstents were manu-factured from polycarbonate based silicone elastomer. Simulated use was performed in a silicone eye model. The presented injector devices were suitable for minimally in-vasive ab interno microstent implantation into suprachoroidal space. Ongoing miniaturization of the microstent system will allow the use of a 22 G cannula in future ex vivo experiments.